Bare Conductive® role as filler in mechanical and electrical reinforcement of polyvinyl alcohol-based strain sensor - Nurul Farhana, Abu Kassim; W. F. W., Idris; Kamal, Yusoh; Zulhelmi, Ismail (IOP Publishing, 2020)
Polyvinyl alcohol (PVA) is a water-soluble polymer typically suited for food and biomedical applications. However, its non-conductive properties limit PVA potential as material in electronic or sensor-based devices. In order to enhance the electrical as well as mechanical properties of PVA, Bare Conductive ® (BC) paste was incorporated into PVA solution using solution intercalation method. It is discovered that the addition of BC could enhance the mechanical and electrical properties of PVA. The tensile test data showed that the presence of carbon black in BC had resulted in the tensile stress improvement at about 50-170 % as compared to that of the original value. On the other hand, the electrical conductivity of PVA/BC composite film at a higher wt% had demonstrated a significant increment in resistance/length ratio (1.86 kΩ/cm at 0.2 wt%BC).